2008
DOI: 10.2341/07-148
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Three Different In-office Bleaching Systems and Their Effect on Enamel Microhardness

Abstract: SUMMARYThis in vitro study evaluated and compared the efficacy of three in-office bleaching systems and investigated their effect on enamel microhardness.Three groups of 12 teeth (third molars) each were bleached as follows: Group A: Opalescence Xtra Boost (38% HP), Group B: Easywhite Ready (30% HP) with plasma unit and Group C: Zoom2 system (25% HP with the Zoom2 unit). The teeth were stained with tea for 24 hours, followed by the appropriate bleaching procedure. Each bleaching cycle was conducted for 15 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 18 publications
3
30
0
3
Order By: Relevance
“…The whitening procedure may lead to dehydration of the teeth, and consequently induce a false, lighter aspect immediately after the end of the session. 26 For this reason, an interval of one week was considered necessupply of the toothpaste type assigned to the group. There were no labels or other types of identification on the toothpaste tubes, only a code for later analysis; both the patient and the operator were blinded.…”
Section: Day 29mentioning
confidence: 99%
“…The whitening procedure may lead to dehydration of the teeth, and consequently induce a false, lighter aspect immediately after the end of the session. 26 For this reason, an interval of one week was considered necessupply of the toothpaste type assigned to the group. There were no labels or other types of identification on the toothpaste tubes, only a code for later analysis; both the patient and the operator were blinded.…”
Section: Day 29mentioning
confidence: 99%
“…Bleaching effect is also affected by heat 8,23) . Although some researches showed that light irradiation accelerated bleaching efficacy 14,23) , other could not find any efficacy of the light irradiation for the bleaching materials without photocatalyst 19,24) . The bleaching effect of H2O2 generally depends on the extent to which hydroxyl radicals are generated.…”
Section: Discussionmentioning
confidence: 99%
“…The tea was used for staining the teeth in many previous studies concerning tooth bleaching 7,8,15,18,19) , as well-known procedure. The type of tea was chosen according to a number of previous experiments, where the stain solution could develop an intrinsic stain, which was consistent with tooth discoloration observed clinically 7,15,18) .…”
Section: Discussionmentioning
confidence: 99%
“…While some authors reported that no adverse effects were observed, others claimed reduction in calciumphosphate ratio and loss of organic components from treated enamel surfaces. Nonetheless, it is highly probable that low pH and hydrogen peroxide oxidation could lead to ultrastructural changes in dentin during internal dental bleaching 16,17) . The purpose of the current study was to compare the efficacies of cold light bleaching of different bleaching durations and the effects thereof on tooth enamel, and thereby identify the optimal bleaching time for cold light bleaching.…”
Section: Introductionmentioning
confidence: 99%